Triangular intuitionistic fuzzy linear system of equations with applications: an analytical approach - Shams, Mudassir; Kausar, Nasreen; Agarwal, Praveen; Shah, Mohd Asif (TAYLOR & FRANCIS LTD, 2024)
This study extended an existing semi-analytical technique, the Homotopy Perturbation Method, to the Block Homotopy Modified Perturbation Method by solving two $ n \times n $ nxn crisp triangular intuitionistic fuzzy (TIF) systems of linear equations. In the original system, the coefficient matrix is considered as real crisp, while the unknown variable vector and right hand side vector are regarded as triangular intuitionistic fuzzy numbers. The Block Homotopy Modified Perturbation Method is found to be efficient and practical to solve $ n \times n $ nxn TIF linear systems as it only requires the non-singularity of the $ n \times n $ nxn TIF linear system's coefficient matrix, whereas the point Homotopy Perturbation Method and other classical numerical iterative methods typically require non-zero diagonal entries in the coefficient matrix. A set of theorems relevant to this study are presented and demonstrated. We solve an engineering application, i.e. a current flow circuit problem that is represented in terms of a triangular intuitionistic fuzzy environment, using the suggested method. The unknown current is then obtained as a triangle intuitionistic fuzzy number. The proposed semi-analytic method is used to solve some numerical test problems in order to validate their performance and efficiency in comparison to other existing techniques. The numerical results of the example are displayed on graphs with different degrees of uncertainty. The efficiency and accuracy of the proposed method are further demonstrated by comparisons to block Jacobi, Adomain Decomposition method, Successive Over-Relaxation method and the classical Gauss-Seidel numerical method.
Keywords: Triangular intuitionistic fuzzy linear system; semi analytical method; iterative methods; computational CPU-time; triangular intuitionistic fuzzy solution; PERTURBATION METHOD; COMPLEX SYSTEM; RANKING METHOD; Engineering; Mathematics